The Synthesis and Characterization of a New Furazan Heterocyclic System - Chavez, David E.; Parrish, Damon A.; Leonard, Philip (Synlett, 2012)
A new furazan macrocycle, hexakis[1,2,5]oxadiazole[3,4-c:3′,4′-e;3′′,4′′-g:3′′′,4′′′-k:3′′′′,4′′′′-m:3′′′′′,4′′′′′-o][1,2,9,10]- tetraazacyclohexadecine was synthesized by oxidation of diamino trifurazan with trichloroisocyanuric acid. A macrocyclic product is formed under the reaction conditions. The product displays interesting structural properties within the trifurazan segments of the molecule, where the central rings are rotated nearly 90° out of plane from the outer rings. The macrocycle has also been shown to be a sensitive explosive with sensitivity and power similar to the explosive pentaerythritol tetranitrate (PETN). The chemical and explosive properties of this new macrocycle are described in this letter.
Keywords: furazan; heterocycle; macrocycle; explosive; azo